(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2013)
Ginger (Zingiber officinale Roscoe) and Lachii (Alpinia allughas Roscoe) are well known and widely used herbs. Ethanol, acetone, methanol and n-hexane extracts of Zingiber officinale Roscoe and Alpinia allughas Roscoe roots were screened for their antioxidant activities in an effort to compare and validate the medicinal potential of their subterranean part. Total phenol (mg gallic acid/g dry matter) and flavonoid contents (catechin equivalents/g dry matter) were estimated by Folin-Ciocalteu and aluminium chloride colorimetric tests respectively. Radical scavenging activity by DPPH methods was expressed as percent inhibition. Total phenolic contents varied from 10 ± 0.12 to 14 ± 0.03 mg gallic acid/g for Z. officinale and 5.46 ± 0.02 to 12.9 ± 0.06 mg gallic acid/g for A. allughas. Total flavonoids were 5.33 ± 0.75 to 8.34 ± 2.1 mg catechin/g for Zingiber officinale and 1.50 ± 0.447 to 9.92 ± 2.5 mg catechin/g for Alpinia allughas in four solvents. Maximum phenolic and flavonoid contents were observed in methanol extracts. The antioxidant activity (percent inhibition) of Zingiber officinale and Alpinia allughas ranged from 26.8 to 68.3 and 14.3 to 58.5 respectively in different solvents. Overall, the findings indicate that the both spices are good sources of phytochemicals which could be exploited as great potentials for drugs and/or nutritional supplements. Bangladesh J. Sci. Ind. Res. 48(2), 115-118, 2013 DOI: http://dx.doi.org/10.3329/bjsir.v48i2.15742